Dopamine Levels Induced by Substance Abuse Alter Efficacy of Maraviroc and Expression of CCR5 Conformations on Myeloid Cells: Implications for NeuroHIV - Matt, Stephanie M.; Nickoloff-Bybel, Emily A.; Rong, Yi; Runner, Kaitlyn; Johnson, Hannah; O’Connor, Margaret H.; Haddad, Elias K.; Gaskill, Peter J. (Frontiers in Immunology, 2021)
Despite the widespread use of antiretroviral therapy (ART), HIV remains a major public health issue. Even with effective ART many infected individuals still suffer from the constellation of neurological symptoms now known as neuroHIV. These symptoms can be exacerbated by substance abuse, a common comorbidity among HIV-infected individuals, but the mechanism(s) by which different types of drugs impact neuroHIV remains unclear. However, all drugs of abuse increase central nervous system (CNS) dopamine, and data show that elevated dopamine increases HIV infection and inflammation in human myeloid cells including macrophages and microglia, the primary targets for HIV in the brain. Thus, drug-induced increases in CNS dopamine may be a common mechanism by which distinct addictive substances alter neuroHIV. Myeloid cells are generally infected by HIV strains that use the chemokine receptor CCR5 as a co-receptor, and our data indicate that in a subset of individuals, drug-induced levels of dopamine could interfere with the effectiveness of the CCR5-inhibitor Maraviroc. One possible explanation for this is that CCR5 can adopt distinct conformations that differentially regulate the efficiency of HIV entry and subsequent replication. Using qPCR, flow cytometry, Western blotting and high content fluorescent imaging, these studies show that dopamine alters the expression of specific conformations of CCR5 on the surface of human macrophages, specifically increasing the amount of CCR5 with an exposed N-terminal domain. These changes are not affected by association with lipid rafts, but do correlate with dopamine receptor gene expression levels, specifically higher levels of D1-like dopamine receptors. These data also demonstrate that dopamine increases HIV replication and N-terminal CCR5 in human microglia similarly to macrophages. Overall, this suggests dopamine plays an important role in the development of neuroHIV and that dopamine signaling pathways should be examined as a target in antiretroviral therapies specifically tailored to HIV-infected drug abusers. These data also support the role of dopamine as an immunomodulatory factor and may have broader implications for the role of dopamine in relation to other diseases.